Systemic Challenges and Coping Strategies in Implementing Curriculum and Assessment Policies in Primary Schools - Seshoka Joseph Rapeta; Rebecca Candice Frank (International Journal of Educational Innovation and Research, 2026)
Background: Primary schools in South Africa continue to face persistent challenges in implementing the Curriculum and Assessment Policy Statement (CAPS), resulting in uneven curriculum delivery and compromised learner outcomes. Purpose: This study examined the systemic obstacles affecting CAPS implementation in the Foundation Phase and explored the coping mechanisms teachers and school leaders employ to navigate these challenges. Methods: A qualitative case study was conducted using Rogan and Grayson’s Curriculum Implementation Framework. Data were generated from semi-structured interviews with 15 participants (Foundation Phase teachers, principals, and Heads of Departments), complemented by document analysis and classroom observations. Thematic analysis was used to identify patterns across data sources. Results: Four major themes emerged: resource constraints, linguistic diversity, stakeholder responsibilities, and teacher preparedness. Teachers reported acute shortages of textbooks and reading resources, where learners shared textbooks. Linguistic diversity posed additional challenges, resulting in slower curriculum coverage and comprehension difficulties. Despite these obstacles, participants employed a range of coping strategies, including collaborative planning sessions, improvised teaching materials, peer mentoring, and multilingual scaffolding strategies to support learners. Conclusions: The study demonstrates that while teachers employ creative coping mechanisms to mitigate systemic obstacles, these strategies cannot fully compensate for persistent structural challenges. Strengthened resource provision, targeted and context-responsive professional development, and improved alignment among key stakeholders are essential to enhancing CAPS implementation and promoting equitable educational outcomes.